KONSEP ADIL POLIGAMI DALAM PANDANGAN M. QURAISH SHIHAB DAN SITI MUSDAH MULIA - Wahyuninto, Liza (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The  purpose of this study  is to first describe  the  views of Quraish  Shihab  and  Siti Musdah  gloriously looking  at polygamy  verses, the practice of polygamy  of the Prophet and  the fair terms of polygamy,  secondly  to describe  a fair concept in polygamy  according  to Quraish  Shihab  and Siti Musdah  Mulia, third to describe  the legal arguments of Quraish  Shihab  and Siti Musdah  His Majesty of fair concepts  in polygamy.  This research  method is literature  research  using qualitative  description research  method. Based on the results of research  and discussion can be drawn the following conclusions:  First, in understand- ing the verses of polygamy,  Quraish  Shihab  argues that based  on the demands of fair treatment of orphans as an accentuation of this paragraph, the context of emphasis  on the command to be fair and polygamy  verses do not make regulations  about  po- lygamy, because it has been  known and implemented by adherents of various shari’a religion and community traditions before the decline of this verse. Siti Musdah Mulia sees that of the whole verse of marriage, First, polygamy  is contrary to the principle and  purpose of marriage  of Islam. Secondly,  QS. An-Nisa verse 3 does  not speak  in the context  of polygamous justification, but in the context of protection for orphans and  women  from injustice behavior. Second, M. Quraish  Shihab  gives insight into the practice of polygamy of the Prophet (s), nor can it be said that Rasulullah SAW marries more than one, and such marriages should  be imitated,  because not all what is done  by the Prophet needs  to be imitated.Sedangkan Siti Musdah  Mulia, the as- sumption  that polygamy  Prophet is a sunnah that can be made  hujjah.  Thirdly, Justice  of polygamy  according  to M. Quraish Shihab  is fair in the field of immaterial  (love). Siti Musdah  Mulia gives the view that there are two main points in looking at the fair concept  in polygamy.  First, the just is meant  not only in terms of material  things such as livelihood but also in the immate- rial matter,  namely  the tendency of love and  compassion. Second, fair criteria covering two aspects  in it, impossible  or hardly anyone can afford to fulfill the prophet SAW